KERJASAMA KEAMANAN MOLDOVA DENGAN UNI EROPA DALAM MENGHADAPI ANCAMAN RUSIA - Fitri, Novirawil; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Moldova, a country bordering Ukraine, has security concerns as a result of Russian threats, and asked the European Union for help in dealing with threats mainly involving the breakaway Transnistria region, as well as increasing cyberattacks. Since the Russian invasion of Ukraine in 2022, cyberattacks against Moldovan institutions have doubled to tripled from 2022 to 2023, mainly targeting government websites, and coinciding with national events. This research uses a qualitative method, with data collection techniques through literature studies sourced from several books, journals, websites, documents and media. This research uses the Realism Perspective and K.J Holsti's International Cooperation Theory as well as the State Level of Analysis. The results showed that the European Union launched a partnership mission in the Republic of Moldova, namely the European Partnership Mission in the Republic of Moldova (EUPM). Since the early 2000s the EU has established a Border Assistance Mission to Moldova and Ukraine (EUBAM) to monitor the Transnistrian Border. It is tasked with establishing monitoring sites, training authorities, and coordinating security measures. The EU also participated in the 5+2 negotiations for a peaceful resolution. The EU is addressing cyber threats in Moldova as a result of Russia's invasion of Ukraine by improving digital infrastructure, supporting cybersecurity programs, and providing assistance. Keywords: Cyber Threats, Moldova Security, Transnitria, European Union.